2011
DOI: 10.1364/oe.19.024795
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of optical absorption enhancement in thin film organic solar cells with plasmonic metal nanoparticles

Abstract: The optical absorption enhancement in thin film organic solar cells (OSCs) with plasmonic metal nanoparticles (NPs) has been studied by means of finite element method with a three-dimension model. It is found that significant plasmonic enhancement of above 100% can be obtained by introducing Ag-NPs at the interface between P3HT:PCBM active layer and PEDOT:PSS anode layer. This enhancement is even larger than that with Ag-NPs totally embedded in the P3HT:PCBM active layer of thin film OSCs. Furthermore, the enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 20 publications
1
47
2
Order By: Relevance
“…Different from Ref. [17], the Ag-NPs are replaced by the Au-NPs to be consistent with the experiment.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Different from Ref. [17], the Ag-NPs are replaced by the Au-NPs to be consistent with the experiment.…”
Section: Introductionmentioning
confidence: 70%
“…Recently, the mechanism of light absorption enhancement of OSCs with metal NPs has been studied theoretically, which indicated that the LSP mode dominates the light absorption enhancement of metal NPs [17]. It is anticipated that, by depositing the metal NPs at the interface between the active layer and the anode layer, the wavelength range of LSP enhancement could be extended for obtaining higher light absorption enhancement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qu et al investigated the influence of the particle position on the solar cell performance [46]. The most efficient location turned out to be the interface between a poly-3,4-ethylenedioxythiophene:polystyrene sulfonate (PEDOT:PSS) charge injection layer and the photoactive layer consisting of poly(3-hexylthiophene):(6,6)-phenyl-C61-butyric-acid-methyl ester (P3HT:PCBM).…”
Section: Colloidal Structures For Light Harvestingmentioning
confidence: 99%
“…This is accomplished by embedding metallic nanoparticles and nanorods into or near the active layer [4][5][6][7]. Similarly, metallic gratings on the top transport conducting layer [8,9] or on the surface of the back silver electrode [10][11][12] have been employed.…”
Section: Introductionmentioning
confidence: 99%